Hi Swami Please don't be angry I just updated your answer for better understanding of solution only.....
Ans: x=-27
4 - (-5) = 9(9 is square of 3)
-5-11=- 16(16 is square of 4)
11- (-14) = 25(25 is square of 5)
-14-22= - 36(36 is square of 6)
22- (x)= 49(square of 7)
->x= -27

4+(-5)=-1
11+(-14)=-3
so it iis having a sequence of odd numbers.In the next sequence we should have"-5" because after the sequence of odd -1 & -3 we have -5.
to get it 22+x=-5
x=-27
simple!!!!!

## Complete the series. 4, -5, 11, -14, 22, ---

This question is related to TCS Interview## Related Answered Questions

## Related Open Questions